Abiotic triggers for sea and river lamprey spawning migration and juvenile outmigration in the River Rhine, Germany. Issue 4 (28th June 2018) - Baer, Jan; Hartmann, Frank; Brinker, Alexander
Abstract: The activity patterns of migrating lampreys (sea lamprey Petromyzon marinus and river lamprey Lampetra fluviatilis ) are poorly understood. This study uses extensive screening data from the cooling water intake of a nuclear power plant on the River Rhine, Germany, gathered on 1308 days over 46 consecutive months between 2011 and 2014. More than 34, 000 lampreys were retrieved, of which the great majority (99.9%) were outmigrating nonfeeding postmetamorphic individuals. The main factors controlling outmigration were season, water temperature and river discharge. The bulk of downstream migration was observed each year in spring at water temperatures between 9 and 12°C, with earlier migrations during significant discharge peaks between December and February. The migration activity of postmetamorphic individuals declined during summer and autumn, regardless of discharge. Turbidity increased the occurrence of postmetamorphic lampreys and supported diurnal migration, which accounted for nearly 20% of all lamprey records. In winter, outmigrating individuals of both species exhibited significantly longer body lengths than those detected during other seasons. Haematophagus postmetamorphic sea lampreys were also retrieved ( n  = 28) and represent the most upstream records of parasitically feeding sea lamprey detected thus far. Adult lampreys migrating upstream were found mainly in spring, but in very low numbers, indicating high prespawning mortalities. The study points to a challenging future for the protection of lampreys in this area: the long duration and the round‐the‐clock nature of the observed migration demand flexible solutions to realise safe operational windows for water intake stations and to minimise impacts on juvenile lampreys.